187 Effects of Oligosaccharide-based Polymer on Growth Performance, Diarrhea, and Fecal β-hemolytic Coliforms in Weanling Pigs Experimentally Infected with a Pathogenic E. coli. (7th May 2021) - Kim, Kwangwook; He, Yijie; Jinno, Cynthia; Yang, Seijoo; Li, Xunde; Bravo, David; Cox, Eric; Liu, Yanhong
Abstract: The objective of this experiment was to investigate dietary supplementation of oligosaccharide-based polymer on growth performance, diarrhea, and fecal β-hemolytic coliforms of weaned pigs experimentally infected with a pathogenic F18 Escherichia coli (E. coli). Forty-eight pigs (7.23 ± 1.11 kg BW) were individually housed in disease containment rooms and randomly allotted to one of four treatments with 12 replicate pigs per treatment. The four dietary treatments were a nursery basal diet (control), and 3 additional diets supplemented with 50 mg/kg Mecadox (AGP), 10 or 20 mg/kg of oligosaccharide-based polymer. The experiment lasted 18 d [7 d before and 11 d after the first inoculation (d 0)]. The doses of F18 E. coli inoculum were 10 10 cfu/3 mL oral dose daily for 3 days. Growth performance was measured on d -7 to 0 before inoculation, and d 0 to 5 and 5 to 11 post-inoculation (PI). Diarrhea score (DS; 1, normal, to 5, watery diarrhea) was daily recorded for each pig. Fecal samples were collected on d 2, 5, 8, and 11 PI to test the percentage of β-hemolytic coliforms in total coliforms. All data were analyzed by ANOVA using the PROC MIXED of SAS with pig as the experimental unit. Inclusion of oligosaccharide-based polymer linearly increased (P < 0.05) ADFI on d 0 to 5 PI, and feed efficiency on d 0 to 5 PI and d 5 to 11 PI (P = 0.07), compared with the control. Supplementation of AGP or oligosaccharide-based polymer reduced (P < 0.01) frequency of diarrhea of pigs from d 0 to 11 PI. No differences were observed in overall growth performance and percentage of fecal β-hemolytic coliforms on d 8 PI among pigs in AGP and oligosaccharide-based polymer treatments. In conclusion, supplementation of oligosaccharide-based polymer enhanced feed efficiency and reduced diarrhea of weaned pigs infected with a pathogenic E. coli.